A Representative Consumer Theory of Distribution - Caselli, Francesco; Ventura, Jaume (American Economic Review, 2000)
This paper introduces various sources of consumer heterogeneity in one-sector representative consumer (RC) growth models and develops tools to study the evolution of the distribution of consumptions, assets, and incomes. These tools are applied to the Ramsey-Cass-Koopmans model of optimal savings and the Arrow-Romer model of productive spillovers. The RC property per se places very few restrictions on the nature of observed distributions, and a wide range of distributive dynamics and income mobility patterns can arise as the equilibrium outcome. An example illustrates how to use these tools to generate quantitative predictions and compare them to the data. (JEL E13, O41)